(untitled) (Physical Education, Health and Social Sciences, 2025)
Objective: The purpose of this study was to compare the modified CT severity index (MCTSI) with the CT severity index (CTSI) regarding assessment of severity parameters in acute pancreatitis (AP). Both CT indexes were also compared with the Acute Physiology, Age, and Chronic Health Evaluation (APACHE II) index. Materials and Methods: Of 397 consecutive cases of AP, 196 (49%) patients underwent contrast-enhanced CT (n = 175) or MRI (n = 21) within 1 week of onset of symptoms. Two radiologists independently scored both CT indexes. Severity parameters included mortality, organ failure, pancreatic infection, admission to and length of ICU stay, length of hospital stay, need for intervention, and clinical severity of pancreatitis. Discrimination analysis and kappa statistics were performed. Results: Although for both CT indexes a significant relationship was observed between the score and each severity parameter (p < 0.0001), no significant differences were seen be- tween the CT indexes. Compared with the APACHE II index, both CT indexes more accu- rately correlated with the need for intervention (CTSI, p = 0.006; MCTSI, p = 0.01) and pan- creatic infection (CTSI, p = 0.04; MCTSI, p = 0.06) and more accurately diagnosed clinically severe disease (area under the curve, 0.87; 95% CI, 0.82–0.92). Interobserver agreement was excellent for both indexes: for CTSI, 0.85 (95% CI, 0.80–0.90) and for MCTSI, 0.90 (95% CI, 0.85–0.95). Conclusion: No significant differences were noted between the CTSI and the MCT- SI in evaluating the severity of AP. Compared with APACHE II, both CT indexes more ac- curately diagnose clinically severe disease and better correlate with the need for intervention and pancreatic infection.